The correct response regarding the equivalence of the two expressions \(2f + 3.6\) and \(3f + 3.6\) is:
The expressions are not equivalent because Ella would get different results when substituting different numbers for f.
This is because the two expressions have different coefficients for \(f\).
To elaborate:
- The first expression \(2f + 3.6\) changes based on the value of \(f\). For example, substituting \(f = 0\) yields \(3.6\), but substituting \(f = 1\) gives \(2(1) + 3.6 = 5.6\).
- The second expression \(3f + 3.6\) also changes with \(f\). Substituting \(f = 0\) yields \(3.6\), but substituting \(f = 1\) gives \(3(1) + 3.6 = 6.6\).
Thus, since they yield different results for \(f = 1\) and have different coefficients for \(f\), they are not equivalent expressions.